Electrocatalysis in Room Temperature Sodium‐Sulfur Batteries: Tunable Pathway of Sulfur Speciation. Issue 7 (12th May 2022) - Wang, Mingli; Zhang, Hong; Zhang, Wenli; Chen, Qianwang; Lu, Ke
Abstract: Benefiting from the merits of natural abundance, low cost, and ultrahigh theoretical energy density, the room temperature sodium‐sulfur (RT NaS) batteries are regarded as one of the promising candidates for the next‐generation scalable energy storage devices. However, the uncontrollable sulfur speciation pathways severely hinder its practical applications. Recently, various strategies have been employed to tune the conversion pathways of sulfur, such as physical confinement, chemical inhibition, and electrocatalysis. Herein, the recent advances in electrocatalytic effects manipulate sulfur speciation pathways in advanced RT NaS electrochemistry are reviewed, including the promotion of the nearly full conversion of long‐chain polysulfides, short‐chain polysulfides, and small sulfur molecules. The underlying catalytic modulation mechanism that fundamentally tunes the electrochemical pathway of sulfur species is comprehensively summarized along with the design strategies for catalytic active centers. Furthermore, the challenge and potential solutions to realize the quasi‐solid conversion of sulfur are proposed to accelerate the real application of RT NaS batteries. Abstract : The tunable sulfur redox chemistry opens a promising avenue to unlock full potential of room temperature NaS electrochemistry, and the novel insights into the quasi‐solid sulfur conversion will generate new opportunities for promising real‐applications. This review focuses on the advances of electrocatalytic manipulation of a sulfur speciation pathway in room temperature NaS batteries.